Practical Synthesis of 1,4-Dihydropyridines on Heterogeneous Sulfonicmodified Silica (SBA-15-SO3H) Catalyst Under Mild Condition - Hung, Tran Q.; Phuc, Ban Van; Loan, Pham Th#139; Thanh; Lan Nhi, Do Thi; Nguyen, Hien; Xuan Vu, Hoan; Do, Dang Van; Dang, Tuan Thanh (Current Organic Synthesis, 2023)
Aims: Synthesis of 1,4-Dihydropyridines (1,4-DHP) using heterogeneous catalyst under mild condition. Objective: Our objective is to explore new applications of non-metal heterogeneous catalysts in the synthesis of 1,4-DHP derivatives in a greener and more efficient approach. Methods: A greener and more efficient method for the synthesis of 1,4-DHPs and an asymmetric 1,4-DHP (Felodipine drug) was successfully developed in high yields using a heterogeneous SBA- 15-SO3H catalyst. Results: A series of symmetric 1,4-DHP and an asymmetric 1,4-DHP (Felodipine drug) were successfully prepared in high yields using a heterogeneous SBA-15-SO3H catalyst. Conclusion: The catalyst, SBA-15-SO3H, exhibited an efficient catalyst activity for the synthesis of 1,4-DHP derivatives in high yields from the aldehyde, β-ketoester, and NH4OAc as a nitrogen source under mild conditions and short reaction time. Bronsted acid sites of this solid catalyst were figured out to play a key role in this transformation. Interestingly, our catalyst is air-stable and can be recycled at least 5 times without losing catalytic activity.
Keywords: solid acid